FAKTOR-FAKTOR YANG MENDORONG GENERASI Y DALAM MENGADOPSI INOVASI MINUMAN TEH - Florensia Stephanus; Caroline Sutjiono (Jurnal Hospitality dan Manajemen Jasa, 2020)
Abstrak: Penelitian ini dilakukan untuk mengetahui faktor-faktor apa saja dan faktor yang paling berkontribusi mendorong generasi Y dalam mengadopsi inovasi minuman teh. Kuesioner dibagikan kepada 265 responden yang kemudian diolah lebih lanjut menggunakan analisa faktor. Hasil penelitan menunjukan terbentuknya 6 faktor baru, yaitu drink attribute & place, motivation, relative advantage, perceived value, learning & promotion, dan familiarity. Faktor drink attribute & place merupakan faktor yang paling berkontribusi mendorong generasi Y dalam mengadopsi inovasi minuman teh.Kata kunci: Generasi Y, Perilaku Konsumen, Adopsi Inovasi, Inovasi Produk, Inovasi Minuman Teh. Abstract: This research was conducted to find out what factors and the most contributing factor that encourage generation Y to adopt tea beverage innovation. Questionnaires were distributed to 265 respondents which further processed using factor analysis. The research results showed there are 6 factors that were formed, which are drink attributes & place, motivation, relative advantage, perceived value, learning & promotion, and familiarity. Drink attribute & place factor is the most contributing factor that encourage generation Y to adopt tea beverage innovation.Keywords: Generation Y, Consumer Behavior, Innovation Adoption, Product Innovation, Tea Beverage Innovation.